Clinical Outcomes Of Radiofrequency Ablation Versus High Ligation And Stripping In The Management Of Primary Lower Limb Varicose Veins: A Retrospective Cohort Study - Muhammad, Nisar; Elahi, Fazal; Masood, Ayesha; Ahmad, Muhaddis; Marwan, Muhammad (Journal of Neonatal Surgery, 2025)
Background: Primary lower-limb varicose veins are a major cause of chronic limb pain, heaviness, edema, and cosmetic deformity, resulting in significant impairment of quality of life. For decades, conventional surgery with high ligation and stripping (HL/S) has been regarded as the standard treatment modality. However, endovenous radiofrequency ablation (RFA) has emerged as a minimally invasive alternative, offering targeted thermal closure of incompetent veins with reduced tissue trauma, shorter recovery time, and improved postoperative comfort, thereby gaining increasing acceptance in contemporary venous practice. Objective: To compare postoperative outcomes, complication profiles, and early recurrence rates between radiofrequency ablation and high ligation with stripping in the management of primary lower-limb varicose veins. Methodology: This retrospective cohort study included 100 adult patients treated for primary lower-limb varicose veins at Lady Reading Hospital, Peshawar, and Combined Military Hospital (CMH) Peshawar between January 2024 and January 2025. Fifty patients underwent endovenous radiofrequency ablation (RFA) and fifty were managed with conventional high ligation and stripping (HL/S). Data were extracted from medical records and included demographic characteristics, postoperative pain scores, duration of hospital stay, wound-related complications, and recurrence within six months. Patients with recurrent varicose veins, deep venous thrombosis, peripheral arterial disease, or a history of previous venous surgery were excluded. Statistical analysis was performed using SPSS version 24.0. Continuous variables were compared using independent-samples t-tests, while categorical variables were analyzed with chi-square tests. A p-value < 0.05 was considered statistically significant. Results: The overall mean age was 44.8 ± 11.6 years, with no significant age difference between the RFA and HL/S groups (p = 0.48). Pain scores at 24 hours were significantly lower in the RFA group (3.1 ± 1.2) than the HL/S group (5.4 ± 1.6; p < 0.001). Hospital stay was shorter following RFA (1.2 ± 0.5 days) compared with HL/S (2.6 ± 0.8 days; p < 0.001). Minor wound complications occurred in 6% of RFA patients versus 18% of HL/S patients (p = 0.04). Early recurrence was lower in the RFA group (4%) than in the HL/S group (12%), though not statistically significant (p = 0.14) Conclusion: Radiofrequency ablation is associated with superior early postoperative outcomes compared with high ligation and stripping, including significantly reduced pain, shorter hospital stay, and fewer wound-related complications, supporting its use as an effective minimally invasive alternative to conventional surgical management of primary lower-limb varicose veins.